HUBUNGAN ANTARA PERHATIAN ORANGTUA DENGAN MOTIVASI BELAJAR IPA PESERTA DIDIK KELAS V GUGUS IV SOPPENG - muh. fadil nur; muhammad amran; muslimin muslimin; satriani, DH satriani, DH (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
This research is a quantitative research with the type of correlational research which aims 1) to find out the description of the parentsattention of class V Cluster IV students, 2) to find out the description of the science learning motivation of students in class V Cluster IV 3) to find out whether there is a significant relationship between parents attention with the motivation to learn science class V group IV students. The population in this study were all students of class V, cluster IV, Kecamatan Lalabata, Kabupaten Soppeng , totaling 104 students. The sampling technique in this study used a probability sampling technique, namely simple random sampling. The data analysis technique is descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistics, namely the average value and percentage, the description of the family environment and students' motivation to learn science is in the very good category. Then, based on the results of inferential statistical analysis, it shows that the value of t count is greater than the value of t table at a significance level of 5%. Thus H0 is rejected and H1 is accepted. From the results of the study, it was concluded that there was a significant relationship between parent attention and the motivation to learn science for class V group IV students, Kecamatan Lalabata, KabupatenSoppeng.HUBUNGAN ANTARA PERHATIAN ORANGTUA DENGAN MOTIVASI BELAJAR IPA PESERTA DIDIK KELAS VGUGUS IV SOPPENG